2008
DOI: 10.1111/j.1556-4029.2008.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Firearm Deaths by Law Enforcement

Abstract: The use of deadly force during law enforcement is a matter that compels public scrutiny. There were 42 gunshot deaths caused by police over a 4-year period in New York City. The decedents' average age was 31 years and ranged from 17 to 64 years. There were 41 males and one female; and 26 Black, nine Hispanic, and seven White decedents. Ethanol and/or drugs of abuse were detected in 78% (31/40) of the decedents. The vast majority of shootings occurred with the police responding to a crime and 90% of the deceden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
5
19
0
2
Order By: Relevance
“…This was followed by the extremities (35%) and then by the head/neck regions (15%). Similar results were again seen in New York City, with the most gunshot wounds occurring in the torso (50%), followed by the extremities (38%), the head and neck (10%), and the remainder of unknown location . The study conducted in Portugal also found the thorax or abdomen to be the most severely injured body region (59%) .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This was followed by the extremities (35%) and then by the head/neck regions (15%). Similar results were again seen in New York City, with the most gunshot wounds occurring in the torso (50%), followed by the extremities (38%), the head and neck (10%), and the remainder of unknown location . The study conducted in Portugal also found the thorax or abdomen to be the most severely injured body region (59%) .…”
Section: Discussionsupporting
confidence: 76%
“…There were 177 gunshot wounds identified; most common were single gunshot wounds (33%), and the maximum number of gunshot wounds in a single decedent was 21. Half of the gunshot wounds were in the torso, and 38% were in the extremities .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…A study performed on victims of police shootings in New York showed that 28 out of 42 victims suffered 2 or more entry wounds. Use of semi-automatic pistols and the involvement of multiple officers are the explanations offered [22]. No comment can be made about armed forces shooting of terrorists, since those deaths were not examined in Colombo.…”
Section: Discussionmentioning
confidence: 97%
“…The vast majority of decedents were male, and the average age was 32, corresponding to those in other fatal use of force studies (Gill & Pasquale-Styles, 2009). Findings suggest that these fatal incidents are likely to be unplanned police operations effected by general duties police.…”
Section: Time Space and Use Of Forcementioning
confidence: 98%